2006
DOI: 10.1021/la061510v
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Induced Destruction of Giant Vesicles in Methylene Blue Solutions

Abstract: We study the photodecomposition of phospholipid bilayers in aqueous solutions of methylene blue. Observation of giant unilamellar vesicles under an optical microscope reveals a consistent pattern of membrane disruption as a function of methylene blue concentration and photon density for different substrates supporting the vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 29 publications
5
94
0
10
Order By: Relevance
“…Thus, understanding the location of these drugs and their interactions with the cell membrane have become rather important parameters for the targeted design of drugs for photo-activated therapies. 7,8 The complexity of biological membranes makes direct studies very difficult; thus, simple model systems that can mimic the cellular environment, such as micelles and lipid vesicles, have been used. [9][10][11] Lipid vesicles are concentric uni-or multilamellar lipid bilayers that have layer diameters Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding the location of these drugs and their interactions with the cell membrane have become rather important parameters for the targeted design of drugs for photo-activated therapies. 7,8 The complexity of biological membranes makes direct studies very difficult; thus, simple model systems that can mimic the cellular environment, such as micelles and lipid vesicles, have been used. [9][10][11] Lipid vesicles are concentric uni-or multilamellar lipid bilayers that have layer diameters Vol.…”
Section: Introductionmentioning
confidence: 99%
“…However, higher bacterial killing (2.0 log) was observed when PPIX-H 2 O 2 mixture was added to the bacterium followed by light irradiation. The enhanced bacterial killing of PPIX-H 2 O 2 mixture may be explained as suggested by Funk and Krise (2007) which reported that H 2 O 2 may alter the membrane permeability and hence the probability of cellular accumulation of the PS, or it may be due to the fact that the photoreaction would cause membrane disruption which in turn facilitate the penetration of H 2 O 2 into the cell (Caetano et al, 2007). Seaver and Imlay (2011) suggested that higher effect of PDT in the presence of H 2 O 2 could be because PS has an easier transit across the bacterial cell membrane, or the presence of H 2 O 2 may increase the amount of molecular oxygen which improves the ROS formation as suggested by Garcez et al (2011).…”
Section: Discussionmentioning
confidence: 94%
“…[12] Recently, we have prepared fluid dimyristoylphosphatidylcholine (DMPC) bilayers on dithiothreitol (DTT) covered AuA C H T U N G T R E N N U N G (111) by vesicle fusion. [13] The OH-rich DTT monolayer turns the Au surface hydrophilic enough to allow vesicle fusion [14] as revealed by in situ atomic force imaging. Methylene blue (MB) and flavin adenine dinucleotide (FAD) have been used as probes to study molecule transport across the bilayer.…”
Section: Introductionmentioning
confidence: 99%